1999
DOI: 10.1161/01.str.30.12.2585
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial of a Comprehensive Stroke Education Program for Patients and Caregivers

Abstract: Background and Purpose-We report the findings of a randomized controlled trial to determine the effectiveness of a multidisciplinary Stroke Education Program (SEP) for patients and their informal carers. Methods-Two hundred four patients admitted with acute stroke and their 176 informal carers were randomized to receive an invitation to the SEP or to receive conventional stroke unit care. The SEP consisted of one 1-hour small group educational session for inpatients followed by six 1-hour sessions after discha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
208
2
2

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(223 citation statements)
references
References 42 publications
11
208
2
2
Order By: Relevance
“…Knowledge, satisfaction with services and emotional outcome were secondaty measures. Although patient and carer knowledge was greater in the SEP group, there were no significant differences in health status between groups and the carers in the control group had greater social functioning than the carers in the SEP group (Rodgers et al, 1999). The literature suggests that patient and carer knowledge of cognitive problems after stroke is poor and that there is an unmet need for more information (Wellwood et al, 1994;Hangar and Mulley, 1993), in particular, specific individualised information (Wiles et al, 1998) provided in more than one way (Hangar et al, 1998).…”
Section: Providing Information About Strokementioning
confidence: 71%
See 1 more Smart Citation
“…Knowledge, satisfaction with services and emotional outcome were secondaty measures. Although patient and carer knowledge was greater in the SEP group, there were no significant differences in health status between groups and the carers in the control group had greater social functioning than the carers in the SEP group (Rodgers et al, 1999). The literature suggests that patient and carer knowledge of cognitive problems after stroke is poor and that there is an unmet need for more information (Wellwood et al, 1994;Hangar and Mulley, 1993), in particular, specific individualised information (Wiles et al, 1998) provided in more than one way (Hangar et al, 1998).…”
Section: Providing Information About Strokementioning
confidence: 71%
“…Indeed, research has shown that providing packages of support in various forms to patients and carers can increase knowledge and satisfaction (Mant et al, 1998;Rodgers et al, 1999) and reduce caregiver strain (WaUcer et al, 1999), anxiety (Dennis et al, 1997) and psychological distress (Mant et al, 1998). The present study lends support to these findings.…”
Section: Providing Information About Strokementioning
confidence: 99%
“…Lack of knowledge in these areas has been identified as a source of anxiety and worry, and may contribute to patient's failure to achieve their maximal potential. 17 Participants' reports question the appropriateness and effectiveness of current methods of providing information to stroke patients and carers. We need to be clear about the specific information needs of patients and their carers, and further research is needed to evaluate the most timely, appropriate, and effective ways of providing such information.…”
Section: Discussionmentioning
confidence: 99%
“…One RCT was unable to demonstrate improvements in caregiver knowledge, satisfaction, or mood after an educational program initiated within a stroke unit. 548 Two other trials found that caregiver knowledge about stroke and satisfaction improved significantly after an inpatient caregiver educational program 515,585 ; however, there were no significant improvements in caregiver emotional state, burden, or perceived health. Another study found that transitional care initiated during inpatient rehabilitation that covered information about stroke for caregivers resulted in decreased patient institutionalization and mortality but did not significantly change caregiver physical or emotional health.…”
Section: Information On Stroke-related Carementioning
confidence: 99%